Video, action and training in the thematic internship in literacy: the beginning of a research-training - Lucio, Elizabeth Orofino (Revista Hipótese, 2021)
The thematic internship is a curricular component of the Integrated Teacher Education course that establishes a dialogue between theory and practice in the internship field schools. It is an experience lived in the context of the thematic internship in Literacy and presents initial propositions of a study that aims to identify and recognize how the video recording tool of a teaching practice enhances the training of the literacy teacher. The initial analysis allows to conclude that the use of the video, impels the subjects to teaching authorship, constituting an important device for researchers-trainers in the field.
Keywords: Thematic Internship; Literacy; Integrated Degree; Video